اضطراب عوامل التخثر عند مرضى الدِيال - سعيد, حسين; سليمان, ابراهيم; زيد, منير أحمد (Latakia University Journal -Medical Sciences Series, 2019)
تعتبر المضاعفات الخثرية – النزفية من المضاعفات الهامة عند مرضى الديال, حيث تكثر النزوف بأنواعها الهضمية والعصبية..... وعلى النقيض من ذلك نجد ميلا غير طبيعي للتخثر في مرحلة الديال خاصة, يتظاهر بالحوادث الوعائية الدماغية والقلبية وانسداد الناسور الشرياني ـ الوريدي العلاجي. مما يستوجب دراسة سبب التخثر المذكور, وقد ركزت دراستنا على دراسة أهم أسباب الميل للتخثر عند مرضى الديال وهو اضطراب عوامل التخثر, وتأثير عملية الديال على عوامل التخثر. وقد اخترنا في دراستنا الفيبرينوجين لأنة يشكل طليعة الفيبرين الذي يعتبر النهاية الحتمية لعملية الأرقاء الثانوي, فلم نجد اضطرابا يذكر في قيمة الفيبرينوجين بعد الديال, مما يستبعد دوره كسبب في الميل للخثار ويستوجب البحث عن اسباب أخرى لحدوث المضاعفة المذكورة. Thrombotic and bleeding disorders are an important complication in haemo-dialysis [H. D]. Gastro-intestinal and neurologic haemorrhage are frequently found. On other hand there is abnormal tendency for thrombosis especially through Dialysis. They were observed as Cardio – vascular or cerebro - vascular accidents [C,V.A]. So we must study the causes of this complication. In our study, we looked for most causes of thrombosis in [H.D] Coagulative Factors Disorder and the effects of H.D on those factors. We selected fibrinogen in our study because it is a pre – cursor of fibrin which is the last phase of secondary hemostasis. We did not find important disorders after dialysis. So we must look for other causes to such complication.